Causes and timing of the European debt crisis: An econometric evaluation - Valerio Filoso; Carlo Panico; Erasmo Papagni; Francesco Purificato; Marta Vázquez Suarez (Economics and Econometrics Research Institute (EERI), 2017)
According to the literature, two main factors sparked the European debt crisis: (1) macroeconomic imbalances originated by national governments and (2) institutional design flaws leading to feeble response by European authorities; still, economists disagree on the factors' strength. Using Bai and Perron's technique, we contribute to the debate by identifying break dates in Greece, Italy and Spain daily values of 10-year public bonds' interest rates and link them to key political and institutional events. Also, employing GARCH and EGARCH models, we investigate how interest rates spreads' volatility reacted to crucial and long-lasting events. Our results uncover the following facts about the crisis: a) it began in May 2010, while the first aid programme for Greece was approved; b) worsened after summer 2011, as the European authorities hastened restructuring the Greek sovereign debt; c) improved only during summer 2012, when the ECB Governing Council approved a programme for the purchase of sovereign bonds. On the whole, our results point at institutional failures as the main cause of the European debt crisis.
Keywords: G12; G14; H63; 330; European debt crisis; Interest rates; Public debt; Event study